Perancangan Sistem Erp Modul Point Of Sale Berbasis Odoo Pada Banyuwangi Festival Dengan Metode Rapid Application Development - Afrananta, Geldisen; Asih Rumanti, Augustina; Ramadani, Luthfi (Metris: Jurnal Sains dan Teknologi, 2024)
The sales report of SMEs at the Banyuwangi Festival is an indicator of the success of the festival. In the process of collecting the sales report, the Banyuwangi Tourism and Culture Office, as the current responsible party, still does it without an information system, making the management of the sales report of SMEs at the Banyuwangi Festival inefficient. Using the Rapid Application Diagram (RAD) method, the design of an ERP system in the form of a point of sale module based on the Odoo application at the Banyuwangi Tourism and Culture Office and the Banyuwangi Festival SMEs is carried out to obtain an efficient process of collecting the sales report of SMEs at the Banyuwangi Festival. The design using the RAD method is carried out to obtain results that are in line with user needs. The results of this research show that the designed ERP system can improve business process efficiency for institutions and efficient sales management for SMEs. The impact of this research is expected to improve data management accuracy, increase collaboration, and optimize sales of Banyuwangi Festival SME products.